Pleistocenska poledenitev v Logarski dolini - Stojilković, Borut (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The article focuses on the glacial remains from the time of the last glacial maximum in the Logar Valley in the Kamnik-Savinja Alps. The purpose of the work is to reinterpret the findings written so far and the geomorphologic remains from the time of the Pleistocene glaciation and to prepare a new proposal of the circumference of the last glacial maximum in this area. The numerical analysis was based on the findings gained with field work. According to the findings, the maximum glacier extent was drawn and a threedimensional reconstruction of the topography of the surface was created.
Keywords: geomorfologija; geomorphology; Kamnik–Savinja Alps; Kamniško-Savinjske Alpe; ledena doba; ledeniki; Logar Valley, Slovenia; Logarska dolina; pleisticen; Slovenia; Slovenija